Development of Chemical Representation-Based Modules on Materials Interaction Between Particles - Ila Rosilawati; Maya Margareta; Lisa Tania (Universitas Lampung, 2022)
Abstract: Development of Chemical Representation-Based Modules on Materials Interaction Between Particles. This study aims to develop and determine the validity/feasibility of the module, as well as to describe the responses of teachers and students to the chemical representation-based module on the interaction material between particles that was developed. The research design used research and development according to Borg and Gall which only carried out the first five stages. The research data were analyzed using descriptive statistical analysis. The results of expert validation on aspects of content suitability, construction, readability and attractiveness were 78.65%, 77.79%, 71.44% and 77.14% with high criteria. The teacher's responses to aspects of appropriateness of content, construction, readability and attractiveness were 76.95%, 86.12%, 77.80% and 73.87% with high criteria. Students' responses to the attractiveness and readability aspects were 80.1% and 81.56%, respectively, with very high criteria. Based on this, the module based on chemical representation on the interaction material between particles developed is valid and suitable for use as teaching materials in schools.Keywords: module, interaction between particles, chemical representation.DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.06